Legal protection of transferred workers after the enabling of the creation law of work - Sarbini; Slamet Suhartono; Sri Setyadji; Hufron, Hufron (Technium Social Sciences Journal, 2021)
This research is a normative legal research, which focuses on the study of positive law. Efforts to fulfill the rights of workers/labor have been carried out since the promulgation of Law Number 13 of 2003 concerning Manpower. It’s hoped that this law can also fulfill the rights of every worker to be able to work and to receive appropriate benefits for the survival of themselves and their families. However, until now the condition of workers/laborers is still faced with several problems, including low wages, low levels of welfare, and weak legal protection for workers. Legal protection for outsourced workers/laborers after the enactment of the Job Creation Law is increasingly erratic, even no better than when the Manpower Law was enacted. This is because the provisions governing the types of work that can be outsourced are removed. In addition, the entry into force of the Job Creation Law allows for the enactment of a life stew contract for outsourced workers/laborers. This thing certainly benefits the entrepreneur, but disadvantages workers/laborers. During the contract period, the employer may at any time unilaterally decide the outsourcing relationship for certain reasons. Thus the enactment of the Employee Creation Law weakens the legal protection of outsourced workers/laborers.